chaTree: An oTree Addon Allowing Face-to-Face Communication in Online Group Experiments - Timo Promann; Jan-Patrick Mayer; Gerd Muehlheusser; Andreas Roider; Eugen Tereschenko; Niklas Wallmeier (CESifo GmbH, 2025)
This paper presents an oTree addon that allows to include face-to-face communication in the form of a video chat in online group experiments. Group decisions, as opposed to individual decision-making, have recently gained considerable attention. The open-source addon is easy to use, exhibits a lean design, and allows to record communication patterns. It has already been successfully employed in a number of group experiments. We explain how to implement the addon and provide a number of recommendations for smooth functionality.
Keywords: C88; C92; 330; group decisions; video chat; online experiments; experimental software; oTree